The Use of Natural Genetic Diversity in the Understanding of Metabolic Organization and Regulation - Fernie, Alisdair; Klee, Harry (Frontiers in Plant Science, 2011)
The study of metabolic regulation has traditionally focused on analysis of specific enzymes, emphasizing kinetic properties and the influence of protein interactions and post-translational modifications. More recently, reverse genetic approaches permit researchers to directly determine the effects of a deficiency or a surplus of a given enzyme on the biochemistry and physiology of a plant. Furthermore, in many model species, gene expression atlases that give important spatial information concerning the quantitative expression level of metabolism-associated genes are being produced. In parallel, ”top-down” approaches to understand metabolic regulation have recently been instigated whereby broad genetic diversity is screened for metabolic traits and the genetic basis of this diversity is defined thereafter. In this article we will review recent examples of this latter approach both in the model species Arabidopsis thaliana and the crop species tomato (Solanum lycopersicum). In addition to highlighting examples in which this genetic diversity approach has proven promising, we will discuss the challenges associated with this approach and provide a perspective for its future utility